The Higher Education Policy of 'Post-Communist' Countries in the Context of Welfare Regimes (CPP RPS 83/2014) - Czarnecki, Krzysztof (Center for Public Policy Research Papers Series, 2014)
The paper attempts to examine whether higher education policies in 'post-communist' countries, proxied by the Visegrad Group, exhibit features distinct from the classical types of welfare regimes (social-democratic, liberal and conservative) that would allow to classify them under a single label. It also re-examines the relationship of different national approaches to higher education participation and funding with welfare regimes. Policies are operationalized in four general indicators: (1) particpation in tertiary education, (2) educational expenditures, (3) tuition fees and student financial support, and (4) pre-tertiary stratification. Correspondence analysis is used to explore the relationship between the countries and indicators. The strong correspondence between the indicators' values and a given welfare regime has been confirmed. The four 'post-communist' countries belonging to the Visegrad Group seem to exhibit a mixture of conservative and liberal features. However, no regular pattern of higher education policy has been found among them. Thus, no distinct 'post-communist' welfare regime can be identified with regard to this policy.
Keywords: Higher education policy; welfare regime; ‘post-communist’ countries; correspondence analysis